Cerebrovascular stenosis related to tyrosine kinase inhibitor for chronic myeloid leukemia: two illustrative cases - Nozomi Sasaki; Yukiko Enomoto; Takamitsu Hori; Hirofumi Matsubara; Yusuke Egashira; Tsuyoshi Izumo (BMC Neurology)
Abstract Background Tyrosine kinase inhibitors (TKIs) improve prognosis in chronic myeloid leukemia (CML). Nilotinib and ponatinib, second- and third-generation TKIs, respectively, have been reported to cause adverse vascular occlusive events such as myocardial infarction and peripheral arterial disease. However, little is known about the risk of cerebral infarction associated with severe cerebrovascular stenosis, which is a late complication of TKIs. Herein, we report two cases of cerebrovascular stenosis associated with TKIs for CML. Case presentation A 53-year-old man with CML experienced transient right-sided hemiparesis and dysarthria. The patient had been treated with ponatinib for 5 years. Digital subtraction angiography revealed diffuse stenosis with luminal narrowing from the terminal portion of the internal carotid artery (ICA) to the entire M1 length of the middle cerebral artery (MCA). He was diagnosed with hemodynamic cerebral ischemia due to severe intracranial ICA stenosis and underwent superficial temporal artery (STA)-MCA bypass surgery. He had no atherosclerotic factors or immunological serum markers such as vasculitis. As a side effect of TKI therapy was suspected, ponatinib therapy was discontinued. A 74-year-old man treated with nilotinib for CML presented with gait disturbances. Diffusion-weighted magnetic resonance imaging revealed multiple infarctions in the right cerebral hemisphere, and magnetic resonance angiography revealed severe bilateral intracranial ICA and MCA stenosis. The patient underwent a STA-MCA bypass surgery. We discontinued nilotinib treatment. The postoperative course was uneventful. Conclusions CML prognosis has steadily improved with the advent of new TKIs. In the future, reports of cerebrovascular stenosis caused by TKIs for CML may increase and systemic complications may become a problem. We should be aware that some TKIs may cause cerebrovascular stenosis.